(3GdJZjQGJ aj bjeI GdfbhO (B:s (3GdBKGQ h GdYdGL aj GdGbJUGO GdGSdGej (B/s - (3Ndjaj, YjSis ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2011)
(3eONd YGe ddfbhO aj GdGbJUGO GdhVYj h GdGbJUGO GdGSdGej , bjeI GdfbhO h JbdHGJgG , BKGQ GdJZjQGJ aj bjeI GdfbhO , YdGL BKGQ GdJZjQGJ aj bjeI GdfbhO aj GdGbJUGO GdGSdGej , (B.s
(3eQGLY U(B.243s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdfbhOs